High variability in the measurement of HIV primary prevention activities and outcomes. Issue 12 (20th December 2020) - Sekimitsu, Sayuri; DePasse, Jacqueline; Morrison, Michelle; Mahy, Mary; Rice, Brian; Earle, Kristen; Daley, Kate; Larson, Jim; Carter, Anna; Garnett, Geoff P; Holmes, Charles B
Abstract: Introduction: While there is a global consensus on monitoring Human Immunodeficiency Virus (HIV) treatment progress, there has been less attention to the degree of consistency of the measurement of HIV prevention programmes—and the global prevention response is not on‐track to achieve 2020 goals. In this paper, we assess the degree of variability in primary prevention indicators selected by national strategic plans (NSPs) and global stakeholder monitoring and evaluation (M&E) strategies. Methods: We obtained the most recent NSPs from low and middle income Joint United Nations Programme on HIV/AIDS (UNAIDS) Fast‐Track countries, and M&E documents from The Global Fund to Fight AIDS, Tuberculosis and Malaria (The Global Fund), President's Emergency Plan for AIDS Relief (PEPFAR), UNAIDS, the Global HIV Prevention Coalition and the World Health Organization (WHO). We extracted HIV primary prevention indicators from each document, standardized and aggregated them by age/ sex, categorized indicators by topic, and evaluated the frequency of matched indicators between countries and stakeholders. Data were collected between February and April of 2019. Results: Twenty‐one NSPs and five global stakeholder documents were assessed; 736 primary prevention indicators were identified; 284 remained following standardization and aggregation. NSPs contained from 3 to 48 primary prevention indicators, with an average of 23; categories included: HIV education and outreach (17.6%), testing (17.3%) and condom use (16.2%). Of unique national indicators, only 34% was shared between two or more countries. Sixty‐nine per cent was applied in a single country only. 56% of NSP indicators did not appear in any global stakeholder document. Conversely, 42% of global indicators did not appear in any surveyed NSPs. Within global indicators, 63% was only measured by one global body, and no single indicator was measured by all five. Conclusions: These analyses reveal a lack of consensus both between and within countries' and global stakeholders' measurement of HIV prevention. Though some variability is expected, these findings point to a need to refocus attention on achieving greater consensus on a global measurement framework for HIV prevention.